An Unusual Presentation of Leptospirosis in an urban setting as an overlooked cause of multiorgan failure - Alam, Md Tarek; Saber, Sadia; Alam, Rafa Faaria; Hossain, Mohammad Monower (Bangladesh Critical Care Journal, 2019)
Leptospirosis is a life-threatening zoonotic disease of global distribution. It has variable presentation ranging from mild febrile illness to life-threatening complications like acute renal failure, acute hepatic failure, pulmonary hemorrhages and cardiac arrhythmias. We present a case of flu-like illness contracted by working at a poorly hygienic place where the patient experienced progressive pulmonary-renal syndrome two days after admission. Index suspicion and early treatment remains the mainstay of this life threatening zoonotic disease. Bangladesh Crit Care J March 2019; 7(1): 51-54